Pengaruh Digital Financial Literacy terhadap Financial Anxiety Mahasiswa di Indonesia: Perspektif dari Akuntansi Keperilakuan - Pagiling, Novieanty; Meilissa Suade, Yuyun Karystin; Sharon, St. Salmah; Mambu, Bellatrix Kezia; Burhanuddin, Fia Fauziah (Sekolah Tinggi Ilmu Ekonomi SBI, 2025)
Low levels of digital financial literacy pose a challenge to achieving inclusive financial participation. Concurrently, rising mental health issues among youth, particularly university students, reflect psychological stress linked to financial instability. This study adopts a quantitative approach using a survey of 176 purposively selected respondents. Data were analyzed using simple linear regression with classical assumption tests. The findings reveal that digital financial literacy has a positive and significant effect on financial anxiety (p < 0.05), although it explains only 10.3% of its variance. These results highlight the need to enhance digital financial literacy and emphasize the importance of contextual and responsive accounting education in addressing both digital transformation and student mental well-being